The development of hearing in prelingually deaf children with white matter changes in the first year after cochlear implantation. (3rd May 2020) - Shen, Min; Li, Yuan; Long, Mo; Wang, Liyan; Liang, Wei; Chen, Zhongyan; Ma, Yanfang; Guo, Yuran; Bi, Qingling; Zhang, Yang
Abstract: Background: The development of hearing and plasticity of brain after cochlear implantation (CI) for prelingually deaf children with white matter changes (group A) is unclear. Objective: To investigate the development of hearing for children in group A during 1 year after CI activation, compared with non-complicated peers (group B). Materials and methods: Twenty-one and 22 children (average age is about 5 years old) were included in groups A and B, respectively. Questionnaires were used to assess the hearing ability at pre-CI, 1, 6 and 12 months after CI activation (called Mpre, M1, M6, M12 for short). In addition, MMRs to pure tones were investigated at the same three time points after CI. Results: There is no significant difference in scores on questionnaires, MMR incidence, latency or amplitude between children in two groups. Scores on questionnaires showed a significant progressive improvement in two groups during the first year after CI. Furthermore, MMR incidence at M6 was significantly higher than that at M1, and MMR latency at M12 was significantly shorter than that at M1. Conclusions and significance: Prelingually deaf children with white matter changes achieved rapid development and comparable outcomes with CI peers over the first year after CI.